Growth and Optical Properties of Lead‐Free Cs3Bi2Br9 Perovskite Microplatelets. Issue 6 (7th March 2022) - Deng, Fang; Zhang, Jinlei; Wu, Shuyi; Liu, Cihui; Xing, Fangjian; Xu, Jiaqing; Di, Yunsong; Yu, Liyan; Dong, Lifeng; Gan, Zhixing
Abstract : Lead‐free halide perovskites are drawing increasing interest due to their environmental friendliness, good thermal stabilities, and unique optoelectronic properties. Herein, a simple and rapid wet‐chemical approach is developed to synthesize the lead‐free Cs3 Bi2 Br9 microplatelets (MPs) with regular hexagonal shapes (side length of ≈5–12 μm). A strong photoluminescence (PL) emission located at 425 nm and a very weak PL band located at 576 nm are observed, which are ascribed to the intrinsic band‐edge transition and the emissive deep level defects, respectively. The weak emission at 576 nm implies the good crystalline quality of the as‐prepared Cs3 Bi2 Br9 MPs. Spatially resolved PL and Raman mappings exhibit inhomogeneous distributions. Both the PL emissions and Raman scatterings at the edges are remarkably stronger than those at the center, which are interpreted by the formation of whispering‐gallery modes (WGMs) due to the optical resonance of cavity, as supported by our finite‐difference time‐domain (FDTD) simulations. Therefore, the hexagonal Cs3 Bi2 Br9 MPs can act as optical cavities, which will play important roles in micro‐waveguides and micro‐lasers that are significant for the development of integrated photonic chips. Abstract : A simple approach is developed to synthesize the lead‐free Cs3 Bi2 Br9 microplatelets (MPs) with regular hexagonal shapes (side length of ≈5–12 μm). Both the photoluminescence emissions and Raman scatterings at the edges are remarkably stronger than those at the center, which are interpreted by the formation of whispering‐gallery modes.